(3GSJQGJjLjI GOGQI GdehGQO GdHTQjI HGdGfOjI GdQjGVjI GdeMJQaI h eSGgeJgG aj GfLGM GdGMJQGa GdQjGVj aj cQI GdbOe HGdLRGFQ (B: (3OQGSI ejOGfjI HGdGfOjI GdQjGVjI GdLRGFQjI GdeMJQaI dcQI GdbOes - (3eYRhR , TYjHs; (3YeQGf, GMeO Mcjes; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2022)
(3gOaJ GdOQGSI GdMGdjI Edi GdJYQa Ydi ESJQGJjLjI EOGQI GdehGQO GdHTQjI Ydi eSJhi GdCfOjI GdQjGVjI GdeMJQaI heSGgeJgG aj EfLGM GdGMJQGa GdQjGVj aj cQI GdbOe HGdLRGFQ, MjK Je GdGYJeGO Ydi GdefgL GdhUaj, hGdbjGe HJUeje GSJeGQJj GSJHjGf cCOGI dLeY GdHjGfGJ, GSJeGQI GSJHjGf Chdi JNU GdeJZjQ GdeSJbd (B((3HESJQGJjLjI EOGQI GdehGQO GdHTQjI(B)(3, hGSJeGQI GSJHjGf KGfjI JNU GdeJZjQ GdJGHY (B((3GdGMJQGa GdQjGVj(B)(3, hHYO GdJMbb ef UdGMjJgeG (B((3GdKHGJ, GdUOb(B) (3Je JhRjYgeG Ydi CYVGA GdCfOjI GdQjGVjI GdeMJQaI eeKdhf aj YjfI GdOQGSI GdJj bhGegG (B(64) (3YVh Je GNJjGQge HWQjbI YThGFjI HSjWI(B. (3haj GdCNjQ Je GdJhUd Edi GdfJGFL GdJGdjI(B: " (3JSGge ESJQGJjLjI EOGQI GdehGQO GdHTQjI GdeWHbI Ydi eSJhi GdCfOjI GdQjGVjI GdeMJQaI aj EfLGM GdGMJQGa GdQjGVj aj cQI GdbOe HGdLRGFQ(B. " -(3JSGge ESJQGJjLjI GdMUhd Ydi GdehGQO GdHTQjI GdeWHbI Ydi eSJhi GdCfOjI GdQjGVjI GdeMJQaI aj EfLGM GdGMJQGa GdQjGVj aj cQI GdbOe HGdLRGFQ (B" (3ESJQGJjLjI JfejI GdehGQO GdHTQjI GdeWHbI Ydi eSJhi GdCfOjI GdQjGVjI GdeMJQaI JSGge aj EfLGM GdGMJQGa GdQjGVj aj cQI GdbOe HGdLRGFQ (B" (3JSGge ESJQGJjLjI JYhjV hecGaCI GdehGQO GdHTQjI GdeWHbI Ydi eSJhi GdCfOjI GdQjGVjI GdeMJQaI aj EfLGM GdGMJQGa GdQjGVj aj cQI GdbOe HGdLRGFQ (B" (3dG JhLO aQhb PGJ OdGdI EMUGFjI aj GJLGgGJ CaQGO YjfI GdOQGSI deSGgeI ESJQGJjLjI EOGQI GdehGQO GdHTQjI GdeWHbI Ydi eSJhi GdCfOjI GdQjGVjI GdeMJQaI aj EfLGM GdGMJQGa GdQjGVj aj cQI GdbOe HGdLRGFQ JHYG deJZjQGJ (B((3GdSf, GdeDgd GdYdej, YOO SfhGJ GdNOeI, GdQJHI GdhXjajI, eSJhi GdfGOj(B) (3GdcdeGJ GdeaJGMjI(B: (3GdESJQGJjLjI, EOGQI GdehGQO GdHTQjI, GdfGOj GdQjGVj GdeMJQa, GdGMJQGa GdQjGVj, cQI GdbOe(B. s
(3OcJhQGIs
Keywords: (3GdGMJQGas; (3GdGfOjI GdQjGVjIs; (3JSjjQ GdehGQO GdHTQjI h GdefTBJ GdQjGVjIs; (3cQI GdbOes